Comparison of the Components of Brainstem Auditory Responses Using Click and Chirp Stimuli in Premature Infants - Seyedeh Maryam Hosseini; Maliheh Mazaher Yazdi; Mohammad Maarefvand; Hasan Haddadzadehniri; Atta Heidari (Function and Disability Journal, 2023)
Background and Objectives: Prematurity means that the baby is born before 37 months of age, which leads to various problems, including hearing defects. Timely detection of hearing loss with the help of tools that facilitate this identification, can have a significant impact on the child’s personal, social, and educational development. The aim of the present study was to achieve better responses using the chirp stimulus along with the click. The chirp stimulus can compensate for the time delay caused by low-frequency stimuli and increases the simultaneous presentation of high and low frequencies in the cochlea. Therefore, the morphology of the waves is improved, and the amplitude of responses increases; thus, the waves can be better identified despite the prematurity of the infants. Methods: Eighy newborns were examined in four groups, which were divided into term and preterm groups based on gestational age (including late preterm, moderate, and very preterm). The intensity of the click and chirp stimuli was fixed at 40 and 80 dB. The amplitude and latency of waves I, III, and V, the inter-peak latencies of I-III, III-V, and I-V, as well as the ratio of the amplitude of wave V/I were among the compared parameters. It should be mentioned in tables paired t-test was used in cases marked with *. Wilcoxon test was used in other cases. Results: The chirp stimulus mainly had less latency than the click stimulus and created a larger amplitude at a high intensity (80 dB). In the intensity close to the threshold, i.e. 40 dB, these findings were slightly different. The more developed the infants, the stronger the responses and the more effective the chirp stimulus in eliciting responses. Conclusion: The chirp stimulus was more effective in obtaining multiple components of brainstem-evoked responses in infants, especially preterm infants, and investigating the status of their auditory system. The use of a higher sample size could lead to an increase in the growth of clinical use and better efficiency of diagnostic protocols and responses.